2012
DOI: 10.1517/17460441.2012.688743
|View full text |Cite
|
Sign up to set email alerts
|

Rhodanine as a scaffold in drug discovery: a critical review of its biological activities and mechanisms of target modulation

Abstract: The biological activity of compounds possessing a rhodanine moiety should be considered very critically despite the convincing data obtained in biological assays. In addition to the lack of selectivity, unusual structure-activity relationship profiles and safety and specificity problems mean that rhodanines are generally not optimizable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(105 citation statements)
references
References 61 publications
3
100
0
2
Order By: Relevance
“…to the market. Thus, 4-thiazolidinones are considered as examples of privileged heterocycles in modern medical/pharmaceutical chemistry [5]. The "classical" directions in the area of development of drug-like small molecules among 4-thiazolidinones are the search of new antimicrobial, anticancer, antidiabetic, anti-inflammatory and antiviral agents.…”
Section: скрининг противовирусной активности в ряду с5 и N3 замещенныхmentioning
confidence: 99%
See 1 more Smart Citation
“…to the market. Thus, 4-thiazolidinones are considered as examples of privileged heterocycles in modern medical/pharmaceutical chemistry [5]. The "classical" directions in the area of development of drug-like small molecules among 4-thiazolidinones are the search of new antimicrobial, anticancer, antidiabetic, anti-inflammatory and antiviral agents.…”
Section: скрининг противовирусной активности в ряду с5 и N3 замещенныхmentioning
confidence: 99%
“…It should be also noted that 5-ylidene-4-thiazolidinone-3-carboxylic acids are among the preferred hitcompounds when using various in silico approaches with the subsequent experimental confirmation of the high affinity level to numerous biological targets [9]. Such findings are often criticized because of reffering 4-thiazolidiones to the so-called "frequent hitters" or "pan assay interference compounds (PAINS)" ("frequent hits" are compounds assigned as high-affinity ligands to the set of biotargets and tend to have a low specificity) [5,10,11]. Although, the debate of the importance of such approach remains open.…”
Section: скрининг противовирусной активности в ряду с5 и N3 замещенныхmentioning
confidence: 99%
“…The anti-microbial activity of rhodanines has been known for over 50 years, and numerous studies have been reported involving the design and synthesis of anti-bacterial agents based on this heterocycle [36][37][38][39]. Furthermore, there has been a recent increase in the number of reports concerning the anti-bacterial activities of N-carboxymethyl rhodanines (Figure 1).…”
Section: Antibacterial Activity Of N-carboxymethyl Rhodaninesmentioning
confidence: 99%
“…TZDs, which are anti-cancer therapeutics for the most common types of cancers including, lung, breast, and colon, have been explored for the PPAR-γ-dependent and -independent mechanisms by which TZDs exert their antitumor effects (5). Rhodanines have been reported to possess antibacterial, antifungal, antiviral, antimalarial, insecticidal, herbicidal, antitumor, anti-inflammatory and cardiotonic activities (6)(7). Besides, rhodanine derivatives are still broadly evaluated for their anticancer activity against different cancer cell lines, often exhibiting selective toxicity against normal cell lines (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%